Survey of collar rot disease incidence of groundnut (Arachis hypogaea L.) Hyper Arid, partially irrigated, north-western plain zone (IC) of Rajasthan - B. D. S. Nathawat; Dinesh Kumar; Raja Ram Choudhary; R.K.Yadav (Annals of Agricultural Research, 2024)
Groundnut (Arachis hypogaea L.) is an important oilseed and legume crop. The growth and development of groundnut is impacted by number of abiotic and biotic factors, which results in qualitative and quantitative yield losses. Survey was conducted in major groundnut growing areas of hyper arid partially irrigated, north-western plain zone (IC) of Rajasthan during kharif 2018 toKharif 2022 to assess the distribution and the incidence of collar rot disease. The highest incidence of collar rot was observed in Shri Dungardh (20.18 %), whereas, least collar rot incidence was observed (13.28%) in Sadulsar. Highest collar rot disease incidence was (18.87%) in Bikaner distract whereas, minimum collar rot (14.08%) incidence was observed in Churu district based on 17 teshils surveyed in  cropping season Kharif 2018 to Kharif 2022.